Pengaruh Motivasi Kerja dan Disiplin Kerja Terhadap Kinerja Karyawan pada PT Rifan Financindo Berjangka di Jakarta - Violita Merisca; Donant Alananto Iskandar (UNIVERSITAS KALBIS, 2022)
The purpose of this study was to find out about work motivation and work discipline on employee performance at PT Rifan Financindo Futures. This type of research is associative, namely research that connects two or more variables. In addition, to determine work motivation and work discipline at PT Rifan Financindo Futures. This research is secondary data type. Data collection techniques by distributing questionnaires to marketing managers are assisted by distributing them to employees at PT Rifan Financindo Berjangka. Through the survey results in this questionnaire, you can see work motivation, work discipline and employee performance.